Effect of creatine supplementation on muscle damage markers and physical performance in volleyball athletes - Santi, Maicon Chigachiaraguti; Galán, Bryan Steve Martínez [UNESP]; Terrazas, Sara Ivone Morhy [UNESP]; De Carvalho, Flávia Giolo; Vieira, Tales Sambrano [UNESP]; Silveira, Glauber Cerizza; Deminice, Rafael; de Freitas, Ellen Cristini [UNESP] (UCAM Universidad Católica de Murcia, 2020)
Given creatine supplementation may attenuate exercise-induced damage and directly influence the ATP-CP system, the purpose of the study is to assess the effects of creatine (Cr) supplementation on muscle damage markers; creatine kinase (CK) and lactate dehydrogenase (LDH), late-onset muscle pain (DOMS) and physical performance in volleyball athletes. A controlled study with a double blind model was performed. Fourteen participants supplemented (0.3 g / kg) of creatine or placebo during (loading phase) and (0.1 g / kg) during (maintenance phase). Significant differences were observed in total plasma creatine concentration (p <0.05), body weight (p = 0.047) and lower pain perception (p = 0.020), 24 hours (p = 0.001), 48 hours (p <0.001) and 72 hours (p = 0.011) in the creatine group. The evaluation of subjective perception of pain verified a significant difference in the creatine group (p <0.05). It was concluded that creatine supplementation, associated with carbohydrate consumption, attenuated the perception of pain in volleyball players after the muscle damage protocol.
Efecto de la suplementación de creatina sobre marcadores de daño muscular y desempeño físico en atletas de voleibol
Keywords: DOMS; Jumping; Muscle injury; Performance